2013
DOI: 10.1038/ncomms3557
|View full text |Cite
|
Sign up to set email alerts
|

Virtual hyperbolic metamaterials for manipulating radar signals in air

Abstract: Microwave beam transmission and manipulation in the atmosphere is an important but difficult task. One of the major challenges in transmitting and routing microwaves in air is unavoidable divergence because of diffraction. Here we introduce and design virtual hyperbolic metamaterials (VHMMs) formed by an array of plasma channels in air as a result of self-focusing of an intense laser pulse, and show that such structure can be used to manipulate microwave beams in air. Hyperbolic, or indefinite, metamaterials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
(24 reference statements)
0
24
0
Order By: Relevance
“…eral configurations, such as in arrays of metallic nanowire embedded in a dielectric host [29], multilayered metal-dielectric structure [30,31], plasma [32,33], metasurface [34], to name a few. These hyperbolic metamaterials have been harnessed for sub-diffraction imaging [35,36], negative-refraction [30,31], photon density of states engineering [37][38][39], heat transfer [40], and so forth.…”
Section: Metamaterials Exhibiting Hyperbolic Dispersion Have Been Promentioning
confidence: 99%
“…eral configurations, such as in arrays of metallic nanowire embedded in a dielectric host [29], multilayered metal-dielectric structure [30,31], plasma [32,33], metasurface [34], to name a few. These hyperbolic metamaterials have been harnessed for sub-diffraction imaging [35,36], negative-refraction [30,31], photon density of states engineering [37][38][39], heat transfer [40], and so forth.…”
Section: Metamaterials Exhibiting Hyperbolic Dispersion Have Been Promentioning
confidence: 99%
“…Pendry and collaborators were early pioneers in designing electromagnetic metamaterials using patterned sub-wavelength standing cylindrical structures [12,13]. Since then, these studies have inspired numerous researchers to realize nanoscale structural analogs, such as silver nanowires [14], doped silicon nanowires [15], and other metallic nanorods [16,17]. The optical anisotropy in such nanowire arrays was identified as a mechanism for negative refraction [18,19].…”
Section: Introductionmentioning
confidence: 97%
“…Previously, it was shown that a rectangular or circular array of plasma filaments can also exhibit anisotropic behavior as above, in which case the mixing rule equations used to determine the permittivity components of the material take the form [17] …”
mentioning
confidence: 99%
“…Here, f is the fill fraction of plasma channels in the filament array given as f = d pl /a pl , where d pl ≈ 50 − 120 m is the diameter of each filament and a pl ≈ 450 − 650 m is the average distance between filaments in the two dimensional case, ε d is the permittivity of the background dielectric material, which is air in this case [17]. The parameter ε fil is the permittivity of each filament, which can be described by the Drude model as…”
mentioning
confidence: 99%
See 1 more Smart Citation